A produção docente e a avaliação dos programas de pós-graduação: um estudo na pós-graduação da UFMT (Revista de Educação Pública, 2012)
O texto analisa as características da produção docente submetida à avaliação dos Programas de Pós-Graduação. A pesquisa tem como fonte o Coleta Capes (CAPES/MEC), segundo a avaliação dos triênios 1998-2000, 2001-2003 e 2004-2006, e considera três Programas da Universidade Federal de Mato Grosso. Conclui que: a) o elemento chave da avaliação é o docente, sobretudo o do quadro permanente; b) os critérios de avaliação destacam a produção intelectual (que se refere às publicações qualificadas) e valorizam as publicações internacionais qualificadas; c) cresceram as atividades docentes de formação e publicações, tendendo a centralizar-se na Pós- Graduação; d) a condição do trabalho docente, de modo geral, reflete a política de avaliação dos Programas.Teacher’s work and the evaluation of the postgraduate programs: A study in the postgraduation of UFMT.AbstractThe text analyses the features of the teacher’s work submitted to the evaluation of the Postgraduate Programs. The source of the research is the Coleta Capes (CAPES/MEC), according to the evaluation of the triennials 1998-2000, 2001-2003 and 2004-2006, and takes into account three Programs of the Federal University of Mato Grosso. It concludes that: a) the key element of the evaluation is the teacher mainly of the permanent staff; b) the evaluation criteria highlights the intellectual production (which refers to the qualified publications) and gives value to the qualified international publications; c) there was an increase in the teacher’s qualification and publications mainly in the postgraduate Programs; d) the teacher’s work, in a general way reflects the evaluation policy of the Programs. Keywords: Evaluation. Postgraduate work. Teacher’s work.